Performance Analysis of Queue Structure in CPU Scheduling Simulation: A FIFO Case Study Using Python - Sanggalie, Dammar; Qolbun Halim Hidayatulloh; Wafiq Ulil Abshor; Putu Novita Darmadewi; Azis Suroni (Journal of Advanced Systems Intelligence and Cybersecurity, 2025)
Queue data structure is an important component in CPU scheduling, especially in the First-Come-First-Serve (FCFS) algorithm that executes processes in the order of arrival. This study aims to analyze the performance of queue structures (deque vs. list) in FCFS CPU scheduling simulations using Python. The simulations are designed to evaluate metrics such as waiting time, completion time, CPU utilization, and throughput, and to identify the convoy effect. The results show that deque (O(1) for append/popleft operations) is 6.22 times faster than list (O(n) for pop(0)) in a 1000-iteration test with a dataset of 10 processes. The convoy effect causes high waiting times for some processes, indicating the limitations of FCFS. This implementation uses a modular object-oriented programming (OOP) approach, providing a basis for further analysis of scheduling algorithms. This study emphasizes the importance of choosing the right data structure for operating system efficiency.